Neuroscience for Medicine and Psychology 2021
DOI: 10.29003/m2172.sudak.ns2021-17/200
|View full text |Cite
|
Sign up to set email alerts
|

HUMAN LACTOFERRIN INCREASES THE EXPRESSION OF TRANSCRIPTION FACTOR c-FOS IN MOUSE BRAIN CELL CULTURE UNDER STIMULATED CONDITIONS

Abstract: Мастер-класс ПРОБЛЕМЫ ОБУЧЕНИЯ НАВЫКАМ ОКАЗАНИЯ ПЕРВОЙ ПОМОЩИ РАЗЛИЧНЫХ СОЦИАЛЬНЫХ ГРУПП Автономная некоммерческая организация дополнительного профессионального образования «Учебно-консультационный центр аварийно-спасательных формирований им. В.В. Никулина», Новомосковск, Тульская обл., Россия Руководитель -Исраилова Татьяна Анатольевна Исраилова Т.А. ПРОБЛЕМЫ ОБУЧЕНИЯ НАВЫКАМ ОКАЗАНИЯ ПЕРВОЙ ПОМОЩИ РАЗЛИЧНЫХ СОЦИАЛЬНЫХ ГРУПП Israilova Tatyana A. ISSUES OF TRAINING FIRST AID PROVISION SKILLS TO VARIOUS SOCIAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Of great interest is the ability of Lf to modulate a whole range of processes by changing the expression of genes encoding some regulatory and effector proteins [ 69 , 70 ]. In our previous studies, we found that in neuronal cultures under conditions of stimulation, Lf enhances the expression of transcription factor c-Fos, a marker of neuronal activity and long-term plasticity [ 71 ]. Lf binding to the surface of immune cells suggests that it can trigger cell reactions such as differentiation, activation, and proliferation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of great interest is the ability of Lf to modulate a whole range of processes by changing the expression of genes encoding some regulatory and effector proteins [ 69 , 70 ]. In our previous studies, we found that in neuronal cultures under conditions of stimulation, Lf enhances the expression of transcription factor c-Fos, a marker of neuronal activity and long-term plasticity [ 71 ]. Lf binding to the surface of immune cells suggests that it can trigger cell reactions such as differentiation, activation, and proliferation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…В наших предыдущих исследованиях было показано, что в нейрональных культурах в условиях стимуляции Лф усиливает экспрессию транскрипционного фактора c-Fos, являющегося маркером нейрональной активности и долговременной пластичности [22]…”
Section: результаты и обсуждениеunclassified